Formation in Social Responsibility of Nursing Professionals: a Brazilian Perspective - Rosa Maria Godoy Serpa da Fonseca; Dulce Aparecida Barbosa; Emiko Yoshikawa Egry (Universidad de Antioquia, 2018)
Abstract: The Brazilian Nursing Association (Associação Brasileira de Enfermagem in portuguese ABEn), since its creation 91 years ago, has been dedicated to the defense of education in nursing at all levels. Given that it is a scientific-cultural entity, it is also responsible for the transmission of the profession's ethos, which in modern societies has also been done through formal education. Additionally, the Association participates strongly on the formulation of public policies in education and health, with representation in numerous instances of government decision. We postulate that nursing education should envision much more than the technical-scientific preparation of the professional graduating from our teaching institutions: its purpose must be that of educating political social subjects capable of acting responsibly and transforming reality, especially in reducing the vast inequalities of the society in which we live, like, for example, lack of access to the healthcare system by a good part of the population.(1)